Register Forschungsförderung der Deutschen Gesellschaft der Plastischen, Rekonstruktiven und Ästhetischen Chirurgen (DGPRÄC) und Forschungsförderungsbericht 2019/2020 = Registry research funding of the German society of plastic, reconstructive and aesthetic surgeons (DGPRÄC) and research funding report 2019/2020 - Möllhoff, Nicholas; Prantl, Lukas; Behr, Björn; Beier, Justus; Daigeler, Adrien; Dragu, Adrian; Eisenhardt, Steffen Ulrich; Fuchs, Paul Christian; Germann, Günter; Hirsch, Tobias; Horch, Raymund; Infanger, Manfred; et al. (Handchirurgie, Mikrochirurgie, plastische Chirurgie, 2021)
Key words Academic Plastic Surgery - Research funding - DFG - BMBF